Fiber Optic Breakthrough: Terahertz Detection of Illegal Drugs - Noor, Khalid Sifulla; Bani, Most. Momtahina; Islam, Md. Safiul; Ferdous, A.H.M. Iftekharul; Hossen, Md. Jakir; Al-Mamun, Abdullah; Badhon, Nasir Uddin (Ital Publication, 2024)
The article presents an illegal drug detector that utilizes photonic crystal fiber (PCF). The fiber structure of the H-PCF comprises a dodecagonal core and circular air gaps in cladding areas. We have analyzed the designed terahertz (THz) frequency range utilizing the Finite Element Method (FEM) and the COMSOL Multiphysics application. The revised design has a high sensitivity in detecting amphetamine (n = 1.518) and cocaine (n = 1.5022) at a frequency of 3 THz, via detection rates of 99.43% and 99.20%, correspondingly. Furthermore, the suggested fiber, which operates at a frequency of 3 THz, has a relatively tiny confinement loss of 4.93×10-08 dB/m and 6.16×10-09 dB/m and a minimal effective material loss of construction of 0.0032 cm-1. In conclusion, it may be stated that drug misuse not only leads to immediate repercussions but also has severe and enduring impacts on human health, potentially resulting in fatality. Hence, it is imperative to accurately and effectively detect illicit substances. H-PCF architecture we offered is well-suited to detect illegal drugs. Doi: 10.28991/ESJ-2024-08-06-019 Full Text: PDF